Porous gold nanospheres by controlled transmetalation reaction: a novel material for application in cell imaging - Shukla, Sourabh; Priscilla, Anie; Banerjee, Meenal; Bhonde, Ramesh R.; Ghatak, J.; Satyam, P. V.; Sastry, Murali (Chemistry of Materials, 2005)
Hollow shell nanostructures have numerous potential applications due to their interesting optical and electronic properties, which can be tuned by varying their shape, size, and shell thickness. In this paper we describe a simple galvanic replacement reaction (transmetalation reaction) involving sacrificial silver nanoparticles and Au(III) ions using a dialysis membrane. The dialysis membrane acts as a partial barrier that provides excellent control over the kinetics of reaction. This process results in the formation of porous gold nanospheres that improve the fluorescence in cell staining by offering an enhanced surface area for binding of the fluorescent dye, propidium iodide (PI). Such porous nanostructures could be ideal candidates for applications such as catalysis, enzyme immobilization, and drug delivery.

Interfacial deposition of Ag on Au seeds leading to AucoreAgshell in organic media - Chandran, S. Prathap; Ghatak, J.; Satyam, P. V.; Sastry, Murall (Journal of Colloid and Interface Science, 2007)
Keywords: core-shell nanoparticles; Gold; HRTEM; interfacial seeded growth; Silver; XPS